1981
DOI: 10.1136/thx.36.9.659
|View full text |Cite
|
Sign up to set email alerts
|

Present outlook in bronchiectasis: clinical and social study and review of factors influencing prognosis.

Abstract: One hundred and sixteen patients with proven bronchiectasis diagnosed at least five years previously were studied to determine the clinical outcome, change in pulmonary function, and degree of social disability. Twenty-two patients had died and the mean duration of follow-up in the survivors was 14 years. The patients who died were characterised by a poorer initial ventilatory capacity than the survivors and cor pulmonale was present in 37 % at the time of death. The survivors showed a tendency for improvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 12 publications
5
62
0
2
Order By: Relevance
“…Bronchiectasis affected a total of 304 (56.8%) out of a possible 535 lobes examined on CT scan. Spirometry showed that airflow obstruction was the predominant finding in this group of bronchiectasis patients, with an average forced expiratory volume in 1 s (FEV1) of 1.85 L?min -1 (65.8% predicted) and forced vital capacity of 3.05 L (88.7% pred), which is in accordance with other studies [15][16][17].…”
Section: No Consent N=9supporting
confidence: 91%
“…Bronchiectasis affected a total of 304 (56.8%) out of a possible 535 lobes examined on CT scan. Spirometry showed that airflow obstruction was the predominant finding in this group of bronchiectasis patients, with an average forced expiratory volume in 1 s (FEV1) of 1.85 L?min -1 (65.8% predicted) and forced vital capacity of 3.05 L (88.7% pred), which is in accordance with other studies [15][16][17].…”
Section: No Consent N=9supporting
confidence: 91%
“…The importance of lung damage occurring after pneumonia, pertussis, measles, or tuberculosis as a cause of bronchiectasis, though often cited (16,24,27,28), is hard to estimate because of inaccurate recall and reporting and the ability of most people to make a full recovery without lasting pulmonary symptoms after these infections (29). We have made the assumption for the purposes of definition that chronic upper respiratory tract symptoms (rhinosinusitis) reflect an underlying airway or immunologic disorder.…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with chronic and frequently purulent expectoration, multiple exacerbations and progressive dyspnoea that can become disabling (Ellis et al, 1981;Cohen and Sahn, 1999;Barker, 2002), and represents a substantial and growing health-care burden. A recent US study demonstrated a marked increased prevalence in older populations varying from 4.2/100 000 adults aged 18-34 years to 271.8/100 000 aged X75 years (Weycker et al, 2005).…”
Section: Introductionmentioning
confidence: 99%